Role of Bicontinuous Structure in Elastomeric Electrolytes for High‐Energy Solid‐State Lithium‐Metal Batteries. Issue 1 (27th November 2022) - Han, Junghun; Lee, Michael J.; Lee, Kyungbin; Lee, Young Jun; Kwon, Seung Ho; Min, Ju Hong; Lee, Eunji; Lee, Wonho; Lee, Seung Woo; Kim, Bumjoon J.
Abstract: Solid‐state lithium (Li)‐metal batteries (LMBs) are garnering attention as a next‐generation battery technology that can surpass conventional Li‐ion batteries in terms of energy density and operational safety under the condition that the issue of uncontrolled Li dendrite is resolved. In this study, various plastic crystal‐embedded elastomer electrolytes (PCEEs) are investigated with different phase‐separated structures, prepared by systematically adjusting the volume ratio of the phases, to elucidate the structure‐property‐electrochemical performance relationship of the PCEE in the LMBs. At an optimal volume ratio of elastomer phase to plastic‐crystal phase (i.e., 1:1), bicontinuous‐structured PCEE, consisting of efficient ion‐conducting, plastic‐crystal pathways with long‐range connectivity within a crosslinked elastomer matrix, exhibits exceptionally high ionic conductivity (≈10 −3 S cm −1 ) at 20 °C and excellent mechanical resilience (elongation at break ≈ 300%). A full cell featuring this optimized PCEE, a 35 µm thick Li anode, and a high loading LiNi0.83 Mn0.06 Co0.11 O2 (NMC‐83) cathode delivers a high energy density of 437 Wh kganode+cathode+electrolyte −1 . The established structure–property–electrochemical performance relationship of the PCEE for solid‐state LMBs is expected to inform the development of the elastomeric electrolytes for various electrochemical energy systems. Abstract : The structure–property–electrochemical performance relationship of the elastomeric electrolyte system is established to demonstrate the importance of balancing Li‐ion transport and mechanical properties for achieving high energy Li metal batteries.